Therapeutic interventions to restore microcirculatory perfusion following experimental hemorrhagic shock and fluid resuscitation: A systematic review. (20th August 2020) - van Leeuwen, Anoek L. I.; Dekker, Nicole A. M.; Jansma, Elise P.; Boer, Christa; van den Brom, Charissa E.
Abstract: Objective: Microcirculatory perfusion disturbances following hemorrhagic shock and fluid resuscitation contribute to multiple organ dysfunction and mortality. Standard fluid resuscitation is insufficient to restore microcirculatory perfusion; however, additional therapies are lacking. We conducted a systematic search to provide an overview of potential non‐fluid‐based therapeutic interventions to restore microcirculatory perfusion following hemorrhagic shock. Methods: A structured search of PubMed, EMBASE, and Cochrane Library was performed in March 2020. Animal studies needed to report at least one parameter of microcirculatory flow (perfusion, red blood cell velocity, functional capillary density). Results: The search identified 1269 records of which 48 fulfilled all eligibility criteria. In total, 62 drugs were tested of which 29 were able to restore microcirculatory perfusion. Particularly, complement inhibitors (75% of drugs tested successfully restored blood flow), endothelial barrier modulators (100% successful), antioxidants (66% successful), drugs targeting cell metabolism (83% successful), and sex hormones (75% successful) restored microcirculatory perfusion. Other drugs consisted of attenuation of inflammation (100% not successful), vasoactive agents (68% not successful), and steroid hormones (75% not successful). Conclusion: Improving mitochondrial function, inhibition of complement inhibition, and reducing microvascular leakage via restoration of endothelial barrier function seem beneficial to restore microcirculatory perfusion following hemorrhagic shock and fluid resuscitation.